Expression of Major Histocompatibility Complex Class I Chain–Related Molecule A, NKG2D, and Transforming Growth Factor–β in the Liver of Humans with Alveolar Echinococcosis: New Actors in the Tolerance to Parasites? - Zhang, Shaoling; Hüe, Sophie; Sène, Damien; Penfornis, Alfred; Bresson-Hadni, Solange; Kantelip, Bernadette; Caillat-Zucman, Sophie; Vuitton, Dominique A. (The Journal of infectious diseases, 2008)
BackgroundEchinococcus multilocularis growth and persistent granuloma, which lead to the development of the severe parasitic disease alveolar echinococcosis (AE), might be caused by abnormal expression of stress-induced proteins, with subsequent abnormalities in T cell activation. Similar to its involvement in tumors, the NKG2D–major histocompatability complex class I chain–related molecules A and B (MICA/B) signaling system could be involved in host-parasite interactions; however, its involvement in helminthic diseases has never been studied MethodsWe studied MICA/B, NKG2D, and transforming growth factor–β (TGF-β) expression on liver sections and measured levels of soluble MICA in serum samples obtained from patients with progressive AE. Livers from healthy and cirrhotic subjects were studied as controls ResultsExpression of MICA/B proteins was strongly enhanced in the hepatocytes and endothelial and bile duct cells; in the CD68+ cells of the periparasitic infiltrate, especially epithelioid and giant cells; and, also, in the metacestode germinal layer. Strong expression of MICA/B in the liver contrasted with low numbers of NK cells and lack of expression of NKG2D on the numerous CD8+ T lymphocytes of the periparasitic infiltrate, as well as with the absence of soluble MICA in serum. TGF-β was strongly expressed by most of the infiltrating lymphocytes ConclusionsSustained expression of MICA/B molecules and TGF-β might lead to modulation of NKG2D with subsequent inhibition of NKG2D-dependent cytotoxicity. Abnormalities of this signaling system could contribute to parasitic evasion of the host’s immunity